Relationship between Growth Mindset and Emotion Management of Pencak Silat Athletes - Megawati Agustiandho; Komarudin; Mochamad Yamin Saputra; Geraldi Novian (Universitas Negeri Semarang, 2025)
In martial arts sports such as pencak silat, physical, technical and mental abilities are required, but often the mentality of athletes is not considered very important by coaches. Pencak silat athletes are often faced with the pressures of competition, failure and stress that affect emotional stability. Growth mindset is believed to influence the way athletes deal with these challenges. This mindset encourages individuals to believe that abilities can be developed through effort and learning so that they have a positive impact on emotional management. The research method used is quantitative with a correlational approach. The instruments used in the study were a growth mindset scale and an emotion management scale given once to the sample. After the data was obtained, data analysis was carried out using the SPSS Version 26 correlation test. The results of this study indicate that there is a significant relationship between growth mindset and the level of self-confidence in pencak silat athletes. Athletes who have a higher growth mindset tend to have better self-confidence in facing challenges and pressures when competing. This is in line with previous findings which state that structured pencak silat training not only improves physical skills, but also strengthens mental and emotional aspects, and can increase athlete confidence. This study concludes that growth mindset and emotional management of Pencak Silat athletes in the preparation stage have a relationship between each other, where growth mindset affects the level of emotional management of Pencak Silat athletes. The findings confirm that psychological aspects, particularly growth mindset, play an important role in managing anxiety and supporting athletes’ performance in the training or competition arena.